(untitled) (Indian Journal of Animal Production and Management, 2025)
This study focuses on the third eyelid gland morphology and histological examination in Cats (Felis catus) and Rabbits. From adult rabbits and cats, ten nictitating membranes were removed and sections examined under a light microscope, and a macroscope. The entire length of a pigmented long, thin, curved structure resembling the eyeball was the dorsal and ventral wings of cartilage — that was only complete in the illustration. Sinus of the ventral wing was less than dorsal wing. There were lymphoid nodules at the bottom of the refractive outside, and the cartilage had two surfaces: the corneal and palmebral. The nictitating gland had an oval shape and seemed to be a [complex acinar gland. The cartilage had isogenous chondrocyte clusters which were diagnosable under a microscope. Further, these results offer relevant reference data in supporting future anatomy studies and treatment about feline third eyelid diseases and aging signs in ocular diseases. Rabbit Nictitating gland Gland is embedded into the conjunctiva and lateral eyelid . It is called semi-circular and smooth in form. From this intricate structure, rich in essential lubrication and protection of the eyes serious and mucous secretions are emitted by a complicated gland. By histology the gland is made up of acinar cells that are cuboidal or column in appearance responsible for fluid secretion, Ductal cells displaying stratified cuboidal or columnar epithelium and help in the transport of secretion, and Myoepithelial cells as the antagonist in expulsion of glandular contents triggered by contraction. The connective stroma of this gland, which keeps it from being squishy and gives it shape, consists of collagen, fibroblasts and elastic fibers. Each of these traits clearly points to the gland possing a unique function with respect to tear secretion and eye health in rabbits.